Effect of scratch velocity on deformation features of C-plane sapphire during nanoscratching - Feng, Pingfa (Strojniški vestnik, 2013)
The effects of scratch velocity on plastic and brittle deformation features of (0001) C-plane sapphire were studied in nanoscratch tests. The test was conducted under a ramping loading condition from 40 N to 200 mN using a nanomechanical test system. A Berkovich nanoindenter was employed in this study. The scratch velocities were set at 2, 4, 8, and 16 m/s. Plastic and brittle deformation features were observed by scanning electron microscopy. The residual stress features of the deformation zones in the scratch groove were observed by Raman spectroscopy. Comparative studies of surface depth profiles and scratch groove features obtained with different scratch velocities reveal that the scratch velocities have distinct effects on the deformation features of C-plane sapphire.
Keywords: brittle deformation; hitrost razenja; krhka deformacija; nano-scratch test; plane sapphire; plastic deformation; plastična deformacija; preoblikovalna hitrost; preostale napetosti; preskus nanorazenja; residual stress; safir, orientiran v ravnini C; scratch velocity